2000
DOI: 10.1089/neu.2000.17.403
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of Mortality and Morbidity After Severe Closed Head Injury

Abstract: Mortality and morbidity of 158 patients with severe head injury were studied in relation to age, and early (24-h) clinical and computed tomography data. For comparison of outcome data in survivors, a group of 32 patients with traumatic injuries to parts of the body other than the head was used as controls. Within the head-injured group, the mortality rate was 51%. Logistic regression analyses combined 13 out of 16 predictors into a model with an accuracy of 93%, a sensitivity of 90%, and a specificity of 95%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(106 citation statements)
references
References 34 publications
9
85
0
8
Order By: Relevance
“…After 2324 duplications removed, 1930 additional articles were excluded on the basis of their titles or abstracts, resulting in the full text of 341 articles being examined. Finally, 20 articles reporting 21 cohort studies were included in the present analysis (Andriessen et al, 2011;Fearnside, Cook, McDougall, & McNeil, 1993;Foulkes, Eisenberg, Jane, Marmarou, & Marshall, 1991;Gomez et al, 2000;Heiden, Small, Caton, Weiss, & Kurze, 1983;Jourdan et al, 2013;Judson, Cant, & Shaw, 1990;Lannoo et al, 2000;Mamelak, Pitts, & Damron, 1996;; L. S. Myburgh et al, 2008;Nordstrom, Messeter, Sundbarg, & Wahlander, 1989;Pang et al, 2007;Petroni et al, 2010;Rusnak, Janciak, Majdan, Wilbacher, & Mauritz, 2007;Selladurai, Jayakumar, Tan, & Low, 1992;Stranjalis et al, 2008;Turazzi, Bricolo, & Pasut, 1984;Turazzi, Bricolo, Pasut, & Formenton, 1987). A flow diagram of the selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After 2324 duplications removed, 1930 additional articles were excluded on the basis of their titles or abstracts, resulting in the full text of 341 articles being examined. Finally, 20 articles reporting 21 cohort studies were included in the present analysis (Andriessen et al, 2011;Fearnside, Cook, McDougall, & McNeil, 1993;Foulkes, Eisenberg, Jane, Marmarou, & Marshall, 1991;Gomez et al, 2000;Heiden, Small, Caton, Weiss, & Kurze, 1983;Jourdan et al, 2013;Judson, Cant, & Shaw, 1990;Lannoo et al, 2000;Mamelak, Pitts, & Damron, 1996;; L. S. Myburgh et al, 2008;Nordstrom, Messeter, Sundbarg, & Wahlander, 1989;Pang et al, 2007;Petroni et al, 2010;Rusnak, Janciak, Majdan, Wilbacher, & Mauritz, 2007;Selladurai, Jayakumar, Tan, & Low, 1992;Stranjalis et al, 2008;Turazzi, Bricolo, & Pasut, 1984;Turazzi, Bricolo, Pasut, & Formenton, 1987). A flow diagram of the selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of traumatic subarachnoid haemorrhage, obliteration of the basal cistern or third ventricle, and non-evacuated haematoma were associated with poorer outcome at 6 months [6,8,21,25,26]. There was strong evidence of no relationship between intraventricular haemorrhage and outcome [7,20,27]. Vital signs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many studies have suggested possible adverse effects of disseminated intravascular coagulation and other coagulopathies on outcome of the patients. [2][3][4][5][6][7] Post-traumatic coagulopathy, in particular, appears to be linked to secondary cerebral injury. 5,8 Although the extent of this process is yet to be elucidated fully, coagulation abnormalities are evident soon after trauma.…”
Section: Introductionmentioning
confidence: 99%